The Roots of Ambivalence: Makiguchi Tsunesaburō’s Heterodox Discourse and Praxis of "Religion" - Gebert, Andrew (Religions, 2022)
In the post-World War II era, Sōka Gakkai has deployed the terminology and concept of "religion" (shūkyō 宗教) in a variety of contexts and to a variety of ends. Do these positions simply reflect a post-war strategic stance? Do they have deeper historical and philosophical roots? A careful reading of key texts by founding president Makiguchi Tsunesaburō 牧口常三郎 (1871-1944) suggests that, from its inception as the Value-Creating Education Society (Sōka Kyōiku Gakkai 創価教育学会) in the 1930s, the movement has occupied an ambiguous space, relative to the conceptualization and practice of "religion", as these were imported at the start of the Meiji Era (1868-1912), adopted and indigenized to respond to the cultural, social and political exigencies of modernizing Japan. Examples of Makiguchi’s heterodoxy, relative to the established understanding of "religion" and its role, include: the rejection of specific ideas of "religion", in relation to education and science, as represented in the writings of such intellectuals as Inoue Tetsujirō 井上哲次郎 and Ishiwara Atsushi 石原純; refusal to accept the official definition of Shintō as non-religion; positing an essential continuity between faith/trust among human subjects and faith directed at ideas and objects typically considered "religious"; promoting the idea of worldly benefit, as a result of faith in and practice of "religion". A careful reading of Makiguchi’s complex, and often heterodox, discourse, relative to the conceptual category of "religion", can frame a more nuanced interpretation of his ultimate heterodoxy—his rejection of the Ise Shrine amulet, an act for which he was arrested and confined to prison in July 1943. It can also clarify the basis for the Sōka Gakkai’s post-war deployments of the concept of religion, and create a more flexible and expansive interpretative space for considering the organization’s discourse and praxis in the post-war era.